Pengaruh Merger, Pergantian Manajemen, Ketidakpuasan Perusahaan, Fee Audit, dan Audit Delay pada Auditor Switching - Nonik Dia Permatasari; Haifah Haifah; Nanda Widaninggar (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2020)
This study was conducted to find the effect of merger, management change, company dissatisfaction, audit fees, audit delay on auditor switching turnover in manufacturing companies listed on the Indonesian Stock Exchange (BEI) in 2014-2018. Data used in this study namely secondary data of companies listed on the Indonesia Stock Exchange in 20142018 with a sample of 76 companies. This study used logistic regression analysis. The results confirmed that (1) the merger variable had no effect on auditor switching (2) management change variable had no effect on auditor switching (3) company dissatisfaction had an effect on auditor switching (4) audit fees had an effect on auditor switching (5) audit delay had an effect on auditor switching.